The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/srt.12582
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of diagnosing seborrheic keratosis by reflectance confocal microscopy

Abstract: It is challenge to diagnose seborrheic keratosis by reflectance confocal microscopy. It may due to the variable clinical and RCM appearances of SK, and limited depth of RCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Reflectance confocal microscopy (RCM) has been applied for non-invasive evaluation of skin tumors. In one study, 390 patients with a clinically suspicious diagnosis of SK were included for RCM 11 . Dermatologists using this method could diagnose SK in 66.2% of patients but not in 24.9% of patients.…”
Section: Non-invasive Diagnosis Beyond the Naked Eyementioning
confidence: 99%
See 1 more Smart Citation
“…Reflectance confocal microscopy (RCM) has been applied for non-invasive evaluation of skin tumors. In one study, 390 patients with a clinically suspicious diagnosis of SK were included for RCM 11 . Dermatologists using this method could diagnose SK in 66.2% of patients but not in 24.9% of patients.…”
Section: Non-invasive Diagnosis Beyond the Naked Eyementioning
confidence: 99%
“…Dermatologists using this method could diagnose SK in 66.2% of patients but not in 24.9% of patients. The authors concluded that the great clinical variability of SKs and the restricted depth reached by RCM limit the use of this method for SK diagnosis 11 .…”
Section: Non-invasive Diagnosis Beyond the Naked Eyementioning
confidence: 99%
“…It is in good agreement with histopathology. It has been used to evaluate a variety of skin diseases, including BCC, 7 SK, 8 melanoma, 9 psoriasis, 10 and acne 11 . Gerger et al 12 and Langley et al 13 evaluated the diagnostic ability of RCM in melanoma tumors, verified the applicability of RCM in differential diagnosis of benign nevus and melanoma, and demonstrated that RCM was more sensitive than dermoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Seborrheic keratosis has a number of varying clinical and histopathologic features and can be challenging to diagnose with RCM 5 . Although streaming of epidermal keratinocytes has been a recognized feature of BCCs, it is important to keep in mind that this process can be seen in several other lesions including seborrheic keratoses.…”
Section: Discussionmentioning
confidence: 99%